Memahami Wacana Pada Iklan Layanan Masyarakat BKKBN Jawa Tengah - Setiawan, Yuliyanto Budi; Fanani, Fajriannoor (Universitas Semarang, 2017)
Central Java BKKBN (Badan Koordinasi Keluarga Berencana Nasional) main objectives is to facilitate government policy in population control. To achieve this objective, BKKBN should treat man and woman in a same respectful way because both have the same contribution to population control. Unfortunately some of their Public Service Announcement (PSA) did not show this emancipation. One of their PSA show only a young woman with her baby, delivering a subtle message that young woman is responsible for early marriage. By using Fairclough s Discourse Analysis, we found that BKKBN Central Java unconsciously construct a discourse through their PSA that young woman not only become the most unbenefited side in the early marriage, but also the most responsible for the marriage.